Poetic Analysis of the Symbols Used in I.Yusupov's Lyrics - Daniyarova G.P (Zien Journals, 2024)
The article provides a poetic analysis of the symbols associated with music used in the lyrics of the national poet, Hero of Uzbekistan I. Yusupov. The connection between words and music is determined by the example of lyrical poems. The article contains ideas about the use of the words muse, lyre in the works of I. Yusupov as a symbol, as well as the mythological hero Orpheus
Keywords: music; lyre; muse; Orpheus